Quality Control Analysis of Woven Fabric Production in the Weaving Process in XYZ with Total Quality Management Method - Isna Nugraha; Restu Hikmah Ayu Murti; Firza Ramadhan; Muhammad Abdus Salam Jawwad; Bekti Nugrahadi; Nur Aini Fauziyah; Reva Edra Nugraha (Nusantara Science and Technology Proceedings, 2022)
XYZ Village is an industrial village that produces woven fabrics. Failure in the production process is something that must be traced to the cause so that it can be used as a basis for improving product quality. Total Quality Management (TQM) is an approach to running a business that tries to maximize the competitiveness of an organization through continuous improvement of products, services, people, processes, and the environment. This study was conducted to identify potential causes of failure and improve the quality of woven fabrics in the weaving process in XYZ Village with the TQM method approach. Based on the calculations that have been done, it was found that there are two valid variables and two other invalid variables because the value of r-count > r-table, namely the variable color is less bright and the color is mixed. Then the main factors that cause the quality of woven fabrics to decrease and result in production failures on woven fabrics are inappropriate battens and also color spots on woven fabrics.